Pengaruh Gender Diversity, Kepemilikan Institusional, Profitabilitas, Dan Leverage Terhadap Pengungkapan CSR Pada Perusahaan Pertambangan Yang Terdaftar Di BEI - Ni Kadek Ayu Yusi Parwati; Luh Gede Kusuma Dewi (Universitas Pendidikan Ganesha, 2021)
This observe goals to describe the effect of gender range, institutional ownership, profitability, and leverage on CSR disclosure in mining businesses listed at the Indonesia stock alternate for the 2015-2019 period. The sort of studies used on this study is quantitative, with statistics in the form of numbers. assets of data used on this observe have been acquired from annual reports posted with the aid of mining organizations on the Indonesia stock change website. the total populace in this have a look at amounted to 44 mining companies indexed at the IDX. The pattern in this study amounted to 85 devices of information evaluation, with the sampling technique the use of purposive sampling accompanied via numerous criteria. In reading the records, the method used is a couple of linear regression analysis that's processed with the assist of SPSS version 21 software program. The consequences of the examine state that gender variety, institutional possession, and profitability in part have a high-quality influence at the disclosure of social obligation or CSR. whilst the leverage variable has a poor impact on the disclosure of social obligation or CSR.